ChemInform Abstract: Catalytic Asymmetric α‐Hydroxyamination of Carbonyls with N‐Hydroxycarbamates Becomes Greener. Issue 39 (23rd September 2014) - Yu, Chenguang; Song, Aiguo; Zhang, Fang; Wang, Wei
Abstract Review: 27 refs.